2015
DOI: 10.1111/jce.12699
|View full text |Cite
|
Sign up to set email alerts
|

Shock Reduction With Multiple Bursts of Antitachycardia Pacing Therapies to Treat Fast Ventricular Tachyarrhythmias in Patients With Implantable Cardioverter Defibrillators: A Multicenter Study

Abstract: This study provides first evidence that a strategy of multiple burst ATP sequences for termination of FVT episodes leads to a clinically meaningful reduction in the need for shocks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
1
23
0
Order By: Relevance
“…However, because our trial was www.nature.com/scientificreports www.nature.com/scientificreports/ designed as an acute study, we are not able to conclude on potential long-term effects of ATP on morbidity and mortality. The use of ATP is well established in ICD therapy, being known for its efficient and painfree termination of slow as well as fast ventricular tachycardias, while reducing ICD shocks and patient discomfort at the same time 1,2,[10][11][12][13] . However, the ongoing international discussion of whether or not ICD therapies themselves lead to an increase in mortality expanded from the initially targeted ICD shocks to ATP.…”
Section: Discussionmentioning
confidence: 99%
“…However, because our trial was www.nature.com/scientificreports www.nature.com/scientificreports/ designed as an acute study, we are not able to conclude on potential long-term effects of ATP on morbidity and mortality. The use of ATP is well established in ICD therapy, being known for its efficient and painfree termination of slow as well as fast ventricular tachycardias, while reducing ICD shocks and patient discomfort at the same time 1,2,[10][11][12][13] . However, the ongoing international discussion of whether or not ICD therapies themselves lead to an increase in mortality expanded from the initially targeted ICD shocks to ATP.…”
Section: Discussionmentioning
confidence: 99%
“…9 Traditionally, a single burst pacing sequence has been used in fast VT. Several recent studies have shown that multiple burst pacing sequences for fast VT (cycle length 250-320 ms) are safe and effective in ICD recipients. 10- 12 Sivagangabalan et al showed that ATP efficacy was low in very fast VT (cycle length 200-250 ms). 13 The safety of ATP delivery needs to be considered in very fast VT.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it is likely that the capability and strengths of ATP as a therapy have not been fully explored to date. 34,35 As a personal preference, a device with ATP capability in the absence of compelling circumstances (e.g., patient preference, access issues) is favored over a subcutaneous device given the effectiveness of ATP. The advent of complex multicomponent systems to address the pacing and ATP deficiencies of the existing subcutaneous ICD is-in this clinician's mind-a needlessly complex, expensive, and unwelcome mouse trap 36,37 (see Figure 6 of Lau et al 37 ).…”
Section: Dr Gimbel Exploresmentioning
confidence: 99%